(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The effective issue of ICT in teaching school subjects in the education system in our country is a topical issue.It is the universal means of education, which allows students to form knowledge, skills and skills, but also to develop personal characteristics, learn.There are several programs in the organization of optional classes on the basis of intensive educational technologies, good results in the organization of modern pedagogical and information technologies.One of them will provide information about the Kahoot program.